Análisis pluriescalar de los patrones de distribución espacial del endemisrno alicantino Vella Lucentina, MB Crespo (Brassicaceae) e implicaciones sobre su conservación - Gras, M.J.; Raventós, J.; Bonet, A.; Ramírez, D.A. (Geographicalia, 2016)
Spatial pattern in plant populations is a key topic in conservation ecology of rare plants. We analyse distribution patterns of rare, endemic shrub Vella lucentina in semi-arid southeastern Spain at macro and mesoescale. Macroescale analysis show a metapopulation pattern whereas mesoescale analyses indicate discontinuities between plant densities related to landuses. In addition these results can offer a conceptual framework for the population management and the conservation of the species.